Using Portable X-ray Fluorescence Spectroscopy for Inexpensive and Quick Determination of Micronutrients in Barley Shoots. Issue 11 (17th June 2022) - Khan, Waleed Amjad; Shabala, Sergey; Cuin, Tracey Ann; Zhou, Meixue; Penrose, Beth
ABSTRACT: Determination of elemental concentrations in plant tissue samples is critically important for analyzing their nutritional content. Micro-elemental analysis mostly relies on inductively coupled plasma (ICP) spectrometry techniques, which are expensive, time-consuming, laborious, and complicated. Portable X-ray fluorescence (pXRF) spectroscopy is widely applied in earth sciences but is rarely practiced to quantify elements in plant samples. In this pilot study, the reliability of pXRF results was compared with that of ICP-mass spectrometer (MS) to determine concentrations of four micronutrients zinc (Zn), iron (Fe), copper (Cu), and cadmium (Cd) in barley ( Hordeum vulgare L.) shoot samples. Ground barley samples were scanned with the pXRF instrument. The concentrations of Zn recorded using this method correlated well with the ICP-MS results ( R 2 = 0.80), while Fe and Cu concentrations showed moderate correlations ( R 2 = 0.57 and 0.42, respectively). However, no significant correlation was found between ICP-MS- and pXRF-derived concentrations for Cd ( p > .05). This work demonstrated the potential of pXRF as a reliable and cost-effective alternative to ICP methods for determining Zn in plant samples as it allows the analysis of a greater number of samples in a short period at considerably less expense.